2023
DOI: 10.3390/genes14061211
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Assessment of Runs of Homozygosity by Whole-Genome Sequencing in Diverse Horse Breeds Worldwide

Abstract: In the genomes of diploid organisms, runs of homozygosity (ROH), consecutive segments of homozygosity, are extended. ROH can be applied to evaluate the inbreeding situation of individuals without pedigree data and to detect selective signatures via ROH islands. We sequenced and analyzed data derived from the whole-genome sequencing of 97 horses, investigated the distribution of genome-wide ROH patterns, and calculated ROH-based inbreeding coefficients for 16 representative horse varieties from around the world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Moreover, our results are consistent with earlier studies that were conducted using Axiom™ Equine Genotyping Array on Russian horse breeds [8]. Other studies involving Arabian and Akhal-Teke breeds have also found high levels of homozygosity; however, given that they studied five individuals of each breed, it cannot be stated that the obtained data are sufficient for a general breed characterization [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our results are consistent with earlier studies that were conducted using Axiom™ Equine Genotyping Array on Russian horse breeds [8]. Other studies involving Arabian and Akhal-Teke breeds have also found high levels of homozygosity; however, given that they studied five individuals of each breed, it cannot be stated that the obtained data are sufficient for a general breed characterization [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…The TMEM45B gene produces the body's hypersensitivity to mechanical pain caused by inflammation and tissue damage [43]. Other authors have found candidate genes in thoroughbred horses that have been implicated in muscle development, among them ADAMTS15 [44], which we also found in a homozygous region in all American Standardbred horses. NTM and OPCML genes are regarded as significant genes in the genomic selection of thoroughbred horses for predicting racing participation [45], and they are also used in the selection of other horse breeds [46].…”
Section: Discussionsupporting
confidence: 53%
“…The candidate genes Sox9 and Sox11 were found to promote the early occurrence of bio mineralization and epiphyseal closure in Debao ponies [51]. The candidate gene ADAMTS15 is associated with muscle development, such as myoblast fusion in thoroughbred horses [69]. ADAMTS have been reported to play an essential role in damaged cartilage tissues and the musculoskeletal system and restrict locomotor functions in horses [70].…”
Section: Discussionmentioning
confidence: 99%